The Discourse of Female Photojournalists: The Imbalance between Remunerated Labor and Maternity as a Professional Calling - Nathalia Cunha da Silva; Elizabeth Moraes Gonçalves (Brazilian Journalism Research, 2018)
This article aims to understand how female photojournalists see maternity within the profession in the contemporary world through the use of a study on the cultural and historical influence of gender roles on the performance and development of female photojournalists in the city of São Paulo. A qualitative methodology was adopted using semi-structured interviews. The interviews were conducted with nine female photojournalists from three different age groups who work both formally and informally. For the purposes of this study, we selected only the parts of the interview where the interviewees referred to their role of mother and professional. The analysis was based on a discursive approach, with theoretical support from French Discourse Analysis. The results show the influence gender roles have on forming symbolic barriers that connect having a career with an imbalance between paid work and maternity.